IMPLEMENTASI PASAL 8 UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN DALAM UPAYA PENCEGAHAN BEREDARNYA TABUNG GAS LPG 3 KG RUSAK ATAU BOCOR OLEH PIHAK PANGKALAN DI PINOH KOTA - Redin Redin (Universitas Kapuas Sintang, 2018)
Conversion of kerosene to gas has a positive impact, because switching from kitchen fuel to gas or LPG causes an increase in demand for 3 kg LPG for households or small and medium enterprises. The magnitude of demand, has an impact on the emergence of 3 Kg LPG gas bases that sell gas directly to consumers. However, the base has responsibility in preventing the circulation of 3 kg broken / leaked LPG tubes before being sold to consumer consumers. The purpose of this study is to find out and examine the implementation of Article 8 of Act Number 8 of 1999 concerning Consumer Protection in an effort to prevent the circulation of LPG 3 gas cylinders kg was damaged / leaked by Pangkalan in Pinoh City of Melawi Regency and to find out the efforts made by the base in preventing the circulation of damaged / leaked 3 kg LPG gas cylinders to consumers in Pinoh Kota. The results of the study revealed that the implementation of Article 8 of Act Number 8 of 1999 concerning Consumer Protection in an effort to prevent the circulation of damaged / leaked 3 Kg LPG gas cylinders by Pangkalan in Pinoh Kota Melawi Regency was properly implemented and in line with the mandate of the law. . It is evident from the absence of consumers who have bought or exchanged tubes in damaged / leaky conditions, meaning that the protection of consumers using 3 kg LPG in Pinoh City Melawi Regency has been carried out by the LPG 3 Kg base properly and responsibly. Thus, the 3 Kg LPG base has tried to prevent the circulation of damaged / leaked 3 kg LPG gas cylinders before arriving at consumers in Pinoh, Melawi Regency. This is evidenced by the examination effort every time there is a distribution of tubes from agents to the base before being marketed at the consumer level, the findings of damaged / leaked tubes are stored in special storage warehouses and not sold to consumers with the intention of providing security and safety for consumers user of 3 kg LPG in Pinoh, Melawi Regency. Keywords: Prevention, Consumers, Base, 3Kg LPG Damaged / Leaked.